Ferrites-based thick film with linseed oil as organic vehicle for enhanced microstrip patch antenna - Hasan, Intan Helina (2018)
Research on microstrip patch antenna (MPA) has been growing in the past few decades due to its planar profile and easy fabrication. Its simplicity of structure which includes a conductive patch, a dielectric substrate, a ground plane and a microstrip feeder is making it more popular for integration in electronic and telecommunication devices focusing on flexibility. There is however few disadvantages of MPA, such as narrow bandwidth, low power and limited material selection if current printed circuit board (PCB) etching fabrication technique is used. Ferrite substrates are known to be able to help overcome this issue, but the dielectric and magnetic properties of bulk ferrites are difficult to control and manipulate. This work aims to solve mentioned problems by using thick film technology which utilizes screen printing method to include ferrite thick film in the MPA structure as substrate overlay to help enhance the bandwidth performance of MPA. Yttrium iron garnet (YIG) and nickel zinc ferrite (NZF) were chosen as the starting ferrite nanopowders. Preparation of the paste by mixing nanopowders with linseed oil as organic vehicle and characterization of the ferrite thick film paste were carried out to investigate properties of the thick film. Results showed that the thick film exhibited moderate permittivity and permeability, which is suitable for MPA fabrication. The actual fabricated MPA with ferrite thick film inclusion on FR4 substrate showed that the thick film improved the performance of MPA with firing temperature of 200°C. MPA with YIG thick film on FR4 substrate exhibited improved return loss and -10dB bandwidth to -35.74 and 0.40 GHz respectively, while Q factor was reduced to 14.00, as compared to MPA with only silver patch which has return loss, -10 dB bandwidth and Q factor of -17.86 dB, 0.26 GHz and 21.54 respectively. As for MPA with NZF thick film, the return loss and bandwidth improved to -29.34 dB, 0.48 GHz respectively, while the Q factor reduced to 11.75. Meanwhile, the same firing temperature did not give same effect to the MPA with ferrite thick film on Kapton substrate. Compared with MPA with only silver patch which has return loss, -10 dB bandwidth and Q factor of - 17.29 dB, 0.88 GHz, 6.41 respectively, the improvement of MPA measurement results occurred when the firing temperature is increased to 300°C. MPA with YIG thick film exhibited improved return loss of -23.67 dB but reduced -10dB bandwidth to 0.70 GHz, while Q factor was increased to 8.4. As for MPA with NZF thick film, the return loss and bandwidth improved to -28.73 dB and 1.16 GHz respectively, while the Q factor reduced to 5.10. As conclusion, a novel ferrite thick film paste with linseed oil as organic vehicle has been successfully developed and characterized. Furthermore, ferrite thick film inclusion in MPA fabrication has proven to enhance the bandwidth of the antenna, leading to a success in fabrication of MPA on flexible substrate with enhanced performance. The flexibility of the antenna may have vast possibilities in various applications in the future, such as wearable antenna, and flexible telecommunication devices.